Dissolution and Stability of Arsenate/Phosphate Fluorapatite Solid Solution [Ca5(PxAs1-xO4)3F] in Aqueous Solution at 25 degree C - Deng, Huan; Mo, Lingyun; Zhu, Yinian; Zhu, Zongqiang; Liu, Huili; He, Na; Liu, Jie (Asian Journal of Chemistry, 2015)
Arsenate/phosphate fluorapatite solid solutions [Ca5(PxAs1-xO4)3F] were synthesized and characterized and then their dissolution was studied at pH 2 at 25 °C. During the dissolution, the aqueous pH and Ca2+ increased quickly at the early stage and achieved a steady state after 48 h. The aqueous F– and PO43– concentrations increased rapidly and achieved a peak value in 1-3 h and then decreased slowly and showed stable after 200-400 h. With the decreasing mole fraction of Ca5(PO4)3F in the solid, the aqueous pH, Ca2+, F– and AsO43– concentrations increased, while the aqueous PO43– concentrations decreased. The F– anion was found to dissolve preferentially and the release of Ca2+ was always more in comparison with the release of PO43– and AsO43–. The dissolution of the phosphate-rich solids followed the Lippmann solutus curve, the dissolution of the arsenate-rich precipitates either followed or slightly overshot the Lippmann solutus curve, then approached the solutus curve.